A New Kind of Art [Based on Autonomous Collective Robotics] - Leonel Moura; Henrique Garcia Pereira (Footprint)
The paper addresses the rationale of a process that produces artworks made by a swarm of robots. This process relies on the interaction, though the environment, of a set of robots designed to create spatiotemporal patterns from an initial homogeneous medium (the canvas). Inspired by social insect societies, the approach presented here exploits robot-robot and robot-environment interactions to develop emergent behaviour. The swarm intelligence concept is crucial to this approach because the viability of the team (group of robots) is required in order to achieve the viability of the individual. Without any central coordination or plan, the group of robots produces its artworks on the basis of a data-driven (bottom-up) process. Moreover, each robot can be viewed as an autonomous agent because it has on board all the resources required to provide the global outcome of the experiment, including sensors, actuators, and the controller, which demonstrates a reactive behaviour by reinforcing a previously made signal (positive feedback). The process is also presented in the context of Machine Art, and a detailed technical description of each robot is given, as well as an example of artworks produced by the collective behaviour of the set of robots.